Docosahexaenoic Acid augments hypothermic neuroprotection in a neonatal rat asphyxia model - BERMAN, Deborah R. (Neonatology, 2013)
BACKGROUND: In neonatal rats, early post-hypoxia-ischemia administration of the omega-3-fatty acid docosahexaenoic acid (DHA) improves sensorimotor function but does not attenuate brain damage. OBJECTIVE: To determine if DHA administration in addition to hypothermia, now standard care for neonatal asphyxial brain injury, attenuates post-hypoxia-ischemia damage and sensorimotor deficits. METHODS: Seven-day-old (P7) rats underwent right carotid ligation followed by 90 min 8% O2 exposure. Fifteen min later, pups received injections of DHA 2.5 mg/kg (complexed to 25% albumin) or equal volumes of albumin. After 1 h recovery, pups were cooled (3 h, 30°C). Sensorimotor and pathology outcomes were initially evaluated on P14. In subsequent experiments, sensorimotor function was evaluated on P14, 21, and 28; histopathology was assessed on P28. RESULTS: At P14, left forepaw function scores (normal: 20/20), were near normal in DHA+Hypothermia-treated animals (mean±SD: 19.7±0.7 DHA+Hypothermia vs. 12.7±3.5 Albumin+Hypothermia, p<0.0001) and brain damage was reduced (mean±SD right hemisphere damage (%) 38±17 DHA+Hypothermia vs. 56±15 Albumin+Hypothermia, p=0.003). Substantial improvements on 3 sensorimotor function measures and reduced brain damage were evident up to P28. CONCLUSION: Unlike post-hypoxia-ischemia treatment with DHA alone, treatment with DHA plus hypothermia produced both sustained functional improvement and reduced brain damage after neonatal hypoxia-ischemia.